A dream of the judgment day: American millennialism and apocalypticism, 1620-1890 - Smith, John Howard (Oxford University Press, 2021)
"The End is near! This phrase, so well known in the contemporary United States, invokes images of manic self-proclaimed prophets of doom standing on street corners shouting their warnings and predictions to amused or indifferent passers-by. However, such proclamations have long been a feature of the American cultural landscape, and were never exclusively the domain of wild-eyed fanatics. A Dream of Judgment Day describes the origins and development of American apocalypticism and millennialism from the beginnings of English colonization of North America in the early 1600s through the formation of the United States and its travails in the nineteenth century. It explores the reasons why varieties of millennialism are an essential component of American exceptionalism, and focuses upon the nation's early history to better establish how millennialism and apocalypticism are the keys to understanding early American history and religious identity. This sweeping history of eschatological thought in early America encompasses not just traditional and non-traditional Christian beliefs in the end of the world, but also how American Indians and African Americans have likewise been influenced by, and expressed, those beliefs in unique ways"--